CASE REPORTSConstrictive pericarditis associated with an ascending aortic aneurysm and aortic valve insufficiency - Jarmoszewicz, Krzysztof; Rogowski, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
We report the case of a 54-year-old patient who was admitted to our institution for planned surgical treatment of an ascending aortic aneurysm and aortic valve insufficiency. A decision was made to perform an elective Bentall-de Bono procedure. Constrictive pericarditis was revealed intraoperatively. The Bentall-de Bono procedure and the resection of calcified pericardium were performed successfully.